2019
DOI: 10.1002/pbc.27931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and providing quality health information for adolescents and young adults with cancer

Abstract: Adolescents and young adults (AYAs, 15-39 years old) are an ideal population to benefit from the ever-expanding number and variety of cancer information and health resources available via the Internet and other digital platforms. However, the ability of individual AYAs to fully utilize such resources depends on their degree of health literacy. Across the trajectory of cancer care, an important role for the oncology clinician is assisting AYAs and caregivers in accessing quality health information consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…They constitute a salient population for digital use to translate and transfer information to improve health outcomes by providing messages geared at the levels of cognitive capacity and psychosocial development. 12 Research indicates gender differences in cancer knowledge, attitudes, and practices. Traditionally males have a history of lower participation in cancer screenings.…”
Section: Introductionmentioning
confidence: 99%
“…They constitute a salient population for digital use to translate and transfer information to improve health outcomes by providing messages geared at the levels of cognitive capacity and psychosocial development. 12 Research indicates gender differences in cancer knowledge, attitudes, and practices. Traditionally males have a history of lower participation in cancer screenings.…”
Section: Introductionmentioning
confidence: 99%
“…The variety of online sources on health- and disease-related topics published on or delivered by the World Wide Web is enormous: websites provided by academic or non-academic institutions, social media, blogs and support forums, patient portals, news aggregators, etc. [ 5 ]. The 2019 survey by Eurostat, the statistical office of the European Union, revealed that “one in two citizens (53%) aged 16–74 reported that they sought online health information related to injury, disease, nutrition, improving health or similar” during the last three months [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this survey it was still an option with a low percentage, but will surely assume greater importance, especially under current pandemic circumstances, which make it necessary to familiarize a high percentage of the population with virtual education. Moreover, the internet is a tool to be considered in health education, but in a targeted way, making reliable sites known, and guiding patients about them [27,28]. A recent work on health information suggests that this may incorporate various methodologies, but in the current era must include digital strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work on health information suggests that this may incorporate various methodologies, but in the current era must include digital strategies. The information should be coordinated by trained health educators in this eld [28]. It is important that health education has clear basic objectives, is programmed from diagnosis, continues over time, and has formative evaluations carried out throughout the disease process to reinforce areas that have not been learned [29].…”
Section: Discussionmentioning
confidence: 99%